Pengaruh Independensi, Pengalaman, Due ProfessionalCare, Etika Dan Tenure Terhadap Kualitas Audit (StudiEmpiris Pada Auditor KAP Surakarta dan Yogyakarta) - Anindito, Hendry, Dr. Triyono, SE, M.Si (2017)
The auditor should be able to maintain and improve the quality of the audit as a result of his work. The purpose of this study was to determine the effect of the independence, experience, due professional care, ethics, and tenur on audit quality. This study uses empirical studies using surveys. The population in this study were all auditors working in KAP Surakarta and Yogyakarta. The sample in this study are some of auditors working in KAP Surakarta and Yogyakarta are listed on Compartment IAI Directory of Certified Public Accountants. The sampling technique used convenience sampling method is sampling based on onvenience. The data obtained from questionnaires required. Data were analyzed using classical assumption test and multiple regression analysis, t test, F test, and test the coefficient of determination.The results showed that: (1) The auditor's independence significant effect onthe quality of the audit results.Value tcount of 3,130 received at standard significance 5% and H1 accepted. The independence of the auditor will affect the improvement ofthe quality of audit results; (2) Work experience auditor significant effect on thequality of the audit results. Value tcount of 3,565 received at standard significance 5%and H2 accepted. Their experience of the auditor's work will have an effect onimproving the quality of audit results; (3) Due care professional auditor significanteffect on the quality of the audit results. Value tcount of 2,515 received at standard significance 5% and H3 accepted. Heightened due professional care auditor willaffect the improvement of the quality of audit results; (4) Ethics auditor significanteffect on the quality of the audit results. Value tcount of 2,305 received at standardsignificance 5% and H4 accepted. Heightened ethical auditor will affect theimprovement of the quality of audit results; (5) Tenur auditor significant effect on the quality of the audit results. Value tcount of 2,372 received at standard significance5% and H5 accepted. Heightened tenur of the auditors will have an effect on improving the quality of audit results; (6) The ndependence, work experience,professional due care, ethics and tenur simultaneously significant effect on thequality of the audit results and the sixth hypothesis (H6) are accepted. The testing ofhypotheses sixth gain in value Fcount > Ftable (28,291 > 2,60) with the value ofp<0,05 accepted at standard significance 5%. Auditor independent, objective, many due professional care, have a lot of high ethics and tenur the better the quality of theaudit results accomplishments